De novo transcriptome sequencing and SSR markers development for Cedrela balansae C.DC., a native tree species of northwest Argentina - Torales, Susana Leonor (2018)
The endangered Cedrela balansae C.DC. (Meliaceae) is a high-value timber species with great potential for forest plantations that inhabits the tropical forests in Northwestern Argentina.Research on this species is scarce because of the limited genetic and genomic information available. Here, we explored the transcriptome of C. balansae using 454 GS FLX Titanium next-generation sequencing (NGS) technology. Following de novo assembling, we identified 27,111 non-redundant unigenes longer than 200 bp, and considered these transcripts for further downstream analysis. The functional annotation was performed searching the 27,111 unigenes against the NR-Protein and the Interproscan databases. This analysis revealed 26,977 genes with homology in at least one of the Database analyzed. Furthermore, 7,774 unigenes in 142 different active biological pathways in C. balansae were identified with the KEGG database. Moreover, after in silico analyses, we detected 2,663 simple sequence repeats (SSRs) markers. A subset of 70 SSRs related to important “stress tolerance” traits based on functional annotation evidence, were selected for wet PCR-validation in C. balansae and other Cedrela species inhabiting in northwest and northeast of Argentina (C. fissilis, C. saltensis and C. angustifolia). Successful transferability was between 77% and 93% and thanks to this study, 32 polymorphic functional SSRs for all analyzed Cedrela species are now available. The gene catalog and molecular markers obtained here represent a starting point for further research, which will assist genetic breeding programs in the Cedrela genus and will contribute to identifying key populations for its preservation.